The data visualization workshop : a self-paced, practical approach to transforming your complex data into compelling, captivating graphics /: a self-paced, practical approach to transforming your complex data into compelling, captivating graphics. (2020) - Döbler, Mario; Grössmann, Tim
No abstract available